Pengaruh Self Esteem, Kompleksitas Tugas, dan Ketidakpastian Lingkungan Pada Senjangan Anggaran - Diah Nirmala Dewi, I Dewa Ayu; Widanaputra, A.A. Gde Putu (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
The purpose of this study is to obtain empirical evidence of the effect of self esteem, task complexity, and environmental uncertainty on budgetary slack in the Nusa Dua Region Star Hotels. This research was conducted at 3, 4 and 5 star hotels in the Nusa Dua Region. The sample used was 234 middle managers in 3, 4, and 5 star hotels in Nusa Dua Region using purposive sampling method and the data analysis technique used was multiple linear regression analysis. Data collection of this research was carried out through questionnaires. Based on the results of this study, it was found that the self-esteem held by hotel management tends to be low and the environmental uncertainty faced is also low so that this will cause budgetary slack. The complexity of the tasks experienced by hotel management tends to be high so that this can also lead to budgetary slack. Keywords : Self esteem, task complexity, environmental uncertainty, budgetary slack.